Investigating the mental health implications of urban environments with neuroscientific methods and mobile technologies: A systematic literature review. (July 2021) - Buttazzoni, Adrian; Parker, Amanda; Minaker, Leia
Abstract: Urbanization is an ongoing global process that is influencing and shaping individual mental health and well-being. This paper aims to provide an overview of the current literature containing state-of-the-art neuroscientific and mobile technologies that have been used to investigate the mental health implications of urban environments. Searches for peer-reviewed primary research articles were conducted in PubMed and SCOPUS, returning 33, 443 papers; 90 empirical articles published from 1981 to 2021 were included in the final synthesis. Central findings suggest virtual reality and mobile electroencephalography to be the most commonly used methods, and demanding mood, affect, and health phenomena or states to be the most common concepts of study in both physical built settings and natural urban spaces. Recommendations for both future practice and study noting particular opportunities for future methodological contributions are discussed. Highlights: Mobile and neuroscience methods offer new ways to study urban mental health topics. We reviewed mobile and neuroscience methods and their related outcomes in this area. Common methods: virtual reality, EEG, GPS/mobile devices, physiological sensors. Affective, mood, and psychological state outcomes were most frequently examined. Conditions, disorders, and function outcomes were relatively less investigated.